Donor-derived cell-free DNA accurately detects acute rejection in lung transplant patients, a multicenter cohort study - Jang, Moon Kyoo; Tunc, Ilker; Berry, Gerald J.; Marboe, Charles; Kong, Hyesik; Keller, Michael B.; Shah, Pali D.; Timofte, Irina; Brown, Anne W.; Ponor, Ileana L.; Mutebi, Cedric; Philogene, Mary C.; et al. (The Journal of heart and lung transplantation, 2021)
Acute rejection, which includes antibody-mediated rejection and acute cellular rejection, is a risk factor for lung allograft loss. Lung transplant patients often undergo surveillance transbronchial biopsies to detect and treat acute rejection before irreversible chronic rejection develops. Limitations of this approach include its invasiveness and high interobserver variability. We tested the performance of percent donor-derived cell-free DNA (%ddcfDNA), a non-invasive blood test, to detect acute rejection. This multicenter cohort study monitored 148 lung transplant subjects over a median of 19.6 months. We collected serial plasma samples contemporaneously with TBBx to measure %ddcfDNA. Clinical data was collected to adjudicate for acute rejection. The primary analysis consisted of computing the area-under-the-receiver-operating-characteristic-curve of %ddcfDNA to detect acute rejection. Secondary analysis determined %ddcfDNA rule-out thresholds for acute rejection. ddcfDNA levels were high after transplant surgery and decayed logarithmically. With acute rejection, ddcfDNA levels rose six-fold higher than controls. ddcfDNA levels also correlated with severity of lung function decline and histological grading of rejection. %ddcfDNA area-under-the-receiver-operating-characteristic-curve for acute rejection, AMR, and ACR were 0.89, 0.93, and 0.83, respectively. ddcfDNA levels of <0.5% and <1.0% showed a negative predictive value of 96% and 90% for acute rejection, respectively. Histopathology detected one-third of episodes with ddcfDNA levels ≥1.0%, even though >90% of these events were coincident to clinical complications missed by histopathology. This study demonstrates that %ddcfDNA reliably detects acute rejection and other clinical complications potentially missed by histopathology, lending support to its use as a non-invasive marker of allograft injury.